The mediating role of attachment in panic disorder and separation anxiety disorder - Mehmet Baltacioğlu; Fatma Gül Helvaci Çelik; Meltem Puşuroğlu (BMC Psychiatry)
Abstract Objective This study aimed to investigate the mediating effect of attachment on the relationship between Panic Dısorder (PD) and Adult Separation Anxiety Disorder (ASAD). Methods 76 patients with PD, who consecutively applied to the Psychiatry outpatient clinic of Rize Recep Tayyip Erdoğan University Training and Research Hospital between 1 April 2023 and 1 December 2023, and 79 healthy individuals were included in the study. The Panic Agoraphobia Scale (PAS), Adult Separation Anxiety Questionnaire (ASA), and Relationship Scales Questionnaire (RSQ) were administered to the participants who voluntarily agreed to participate in the study. Results In the study, it was found that the prevalence of ASAD was statistically significantly higher in patients with PD (66%) than in healthy individuals (34%) (p < 0.05). In the model created to examine the mediating effect of attachment on the relationship between PD and ASAD, it was observed that only ASAD had a direct effect on the development of PD (β = 0.063, 95% CI: 0.053, 0.306, p = 0.006). On the other hand, it was found that attachment styles did not play a mediating role in this relationship, either directly or indirectly (p > 0.05). Conclusion The study found that the prevalence of ASAD and insecure attachment problems was higher in patients with PD compared to healthy individuals. It was observed that there was no mediating effect of attachment in the relationship between PD and ASAD. On the other hand, it was determined that ASAD had a direct effect on the development of PD.